Tafsir sebagai Hermeneutika Islam: Kajian dan Terapan - Fariz Pari (Refleksi: Jurnal Kajian Agama dan Filsafat, 1999)
Tafsir, as an Islamic hermeneutics, holds a significant position in understanding and applying the sacred text of the Qur'an. This study aims to investigate the theoretical and practical aspects of tafsir as an interpretive method within the Islamic tradition. Through an approach of textual and contextual analysis, this research explores various tafsir approaches used in Islamic history and their application in contemporary contexts. The role of tafsir as Islamic hermeneutics lies not only in understanding the meaning of the Qur'anic text but also in connecting it with social, cultural, and political realities. This research also explores the relevance and challenges faced in applying Islamic hermeneutics in contemporary contexts. Through this in-depth analysis, it is hoped to gain a better understanding of the role of tafsir in enriching religious understanding and guiding religious practices in contemporary Islamic society.